PRAGMATICS ANALYSIS OF MAXIM FLOUTING DONE BY THE MAIN CHARACTERS IN KUNGFU PANDA MOVIE BY JONATHAN AIBEL & GLENN BERGER - Triza Hamani; Yulan Puluhulawa (British (Jurnal Bahasa dan Sastra Inggris), 2019)
Abstract Maxims are the rules to know whether the speaker can be cooperative or not while he contributes the information in conversation. By flouting maxims, the participants of the conversation seem to be uncooperative but actually they do. The participants themselves have certain intentions of flouting the maxims. There are some intended meanings and certain purposes which are conveyed by the speaker behind the utterance where maxim flouting occurs. Hence, by flouting the maxims, the participants are not said to beuncooperative in a conversation. It is because maxim flouting is a way to make the hearer look for the real meaning beyond what is said implicitly by the speaker. This research only focus in analyzing maxim flouting that occurs in the Kungfu Panda Movie. This research uses the Grice’s Cooperative Principle and Cutting’s theory they are maxim quantity, maxim quality, maxim relation and maxim of manner that flouting by the main character in Kungfu Panda Movie Script. Based on the data analysis , it has been discovered that all the main characters all flouting all the types of maxims. The maxim of quantity flouting becomes the main type of maxim flouting which is performed by the main characters. They have tendency to flout this maxim to make the information given to the listener clearer. It is done by giving too little information rather than giving much one. Meanwhile, maxim of quality and maxim of manner flouting rarely occurs in the movie because the characters are assertive kind of persons. They avoid giving unclear information which leads the understanding of the hearer. Keywords: Maxim flouting, types, strategies, Kungfu Panda movie